High Performance Triboelectric Nanogenerators from Compostable Cellulose-Biodegradable Poly(Butylene Succinate) Composites - Lapčinskis, Linards; Ģērmane, Līva; Platnieks, Oskars; Krikovs, Artis; Pudzs, Kaspars; Linarts, Artis; Sherrell, Peter C.; Šutka, Andris (Wiley, 2023)
Triboelectric nanogenerator (TENG) devices are exemplar systems for mechanical-to-electrical energy conversion due to their simplicity and promising performance. However, little attention has been paid to recycling or reusing TENG devices. Indeed, most TENG devices are based on non-biodegradable polymers, and thus end up in a landfill. Developing biodegradable triboelectric materials is crucial to mitigate negative environmental impacts from their growing use, however, it is challenging to identify such a materials that generate an applicable charge. Herein, such a biodegradable polymer triboelectric pair is demonstrated, by combining poly(butylene succinate) (PBS) films with microcrystalline cellulose (MCC) filler. A power density of 143 mW m−2 and a charge density of 1.36 nC cm−2 is measured when contacting pristine PBS with 70 wt% MCC/PBS composite film, which is comparable to polydimethylsiloxane-based TENGs under identical testing conditions. These devices are shown to degrade via composting at 58 °C over 70 days, enabling long-term (>10 000 cycle) performance and degradation upon disposal. It is suggested that this approach can be extended to control triboelectric properties for other biodegradable polymers. The technology and concepts developed herein directly address the United Nations Sustainable Development Goals for Responsible Consumption & Production and Affordable and Clean Energy. --//-- This is an open-access article: L. Lapčinskis, L. Ģērmane, O. Platnieks, A. Krikovs, S. Gaidukovs, K. Pudzs, A. Linarts, P. C. Sherrell, A. Šutka, High Performance Triboelectric Nanogenerators from Compostable Cellulose-Biodegradable Poly(Butylene Succinate) Composites. Adv. Sustainable Syst. 2023, 7, 2300280. https://doi.org/10.1002/adsu.202300280 published under the CC BY licence.
This work was supported by Latvian Council of Science in the framework of FLPP “Printed biopolymer 4D TENG device for mechanical energy harvesting” (lzp-2022/1-0485). Roughness measurements were performed on equipment located at the Center of Excellence at the Institute of Solid State Physics, University of Latvia, which was supported by European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2. P.C.S. acknowledges support from RMIT University through the RMIT Vice-Chancellor's Research Fellowship Scheme.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics